Observed Evidence for Steep Rise in the Extreme Flow of Western Himalayan Rivers. Issue 15 (7th August 2020) - Chug, Divyansh; Pathak, Amey; Indu, J.; Jain, Sharad K.; Jain, Sanjay K.; Dimri, A. P.; Niyogi, Dev; Ghosh, Subimal
Abstract: We present the first observational evidence of changing patterns of extreme streamflows at multiple locations across Western Himalayan (WH) rivers. We find that the frequency of extreme flow events during the period 1980–2003 has doubled with a statistically significant increasing trend in annual maximum streamflow. We postulate that this streamflow change is due to the increased precipitation extremes occurring during both the summer monsoon and the winter seasons. We further found a stepwise increase of "chi‐gradient" in Bhagirathi and Sutlej Rivers, indicative of a landscape that facilitates rapid flow of water generating severe floods downstream. Our results highlight the severity of hydroclimatic changes underway in the WH region and the critical need for a hydro‐infrastructure for flood forecasting to benefit more than 17 million inhabitants and for ecosystem services to mitigate increasing flood hazards. Plain Language Summary: Flooding in the Western Himalayan rivers has caused colossal loss of life and property in the recent decades. We present a first analysis of changing patterns of observed peak streamflow in Western Himalayan rivers at multiple locations, using high‐quality in situ data. With a high degree of confidence, we conclude that the occurrence of extreme flow events during the period of 1980–2003 has doubled with an increasing trend in annual maximum streamflow. Our analysis shows that this streamflow change is due to the increased precipitation extremes during both the summer monsoon and the winter seasons. We also found that the profiles of two Western Himalayan rivers (Bhagirathi and Sutlej) exhibit steep slopes in a stepwise manner, indicative of a landscape that rapidly responds to extreme precipitation by contributing to severe floods. Our results contextualize the severity of hydroclimatic changes underway in the WH region. Results also highlight the critical need for a hydro‐infrastructure and an operational flood forecasting system to benefit more than 17 million inhabitants and for ecosystem services to mitigate increasing flood hazards. Key Points: First evidence from observations shows that occurrences of extreme streamflow in Western Himalayan rivers have doubled during 1980–2003 Increasing trends of rainfall extremes and the geomorphology of the rivers have driven the dramatic increase in extreme streamflow There is a critical need for a dedicated, high‐resolution, real‐time flood forecasting system for the Western Himalayan region